Evaluación del potencial del sector metal mecánico : el caso de 8 empresas del valle del cauca - Graffe Morales, Luis Felipe (Universidad de San Buenaventura - Cali, 2016)
In this work is presented, the evaluation of the potential of the metalworking sector specifically the case of 8 companies of Valle del Cauca. In terms of value added and the competitiveness that the sector reflects a lag occurs by net export trend of the Colombian nation and causing a technological gap in terms of added value. To account for the stated objective , it was proposed to describe the added value of the metallurgical production in the case of the 8 companies and promotional tools to promote the development potential of the sector We conclude that there is in the engineering sector a tendency for organizations in this sector by improving production and establishment of competitiveness and also strategies and public policies of the Colombian government.